RETRACTED ARTICLE: Enhanced post-quantum key escrow system for supervised data conflict of interest based on consortium blockchain - Xu, Shiwei; Sun, Ao; Ren, Zhengwei; Zhao, Yizhi; Ni, Qiufen; Tong, Yan (Journal of combinatorial optimization, 2023)
Consortium blockchains offer privacy for members while allowing supervision peers access to on-chain data under certain circumstances. However, current key escrow schemes rely on vulnerable traditional asymmetric encryption/decryption algorithms. To address this issue, we have designed and implemented an enhanced post-quantum key escrow system for consortium blockchains. Our system integrates NIST post-quantum public-key encryption/KEM algorithms and various post-quantum cryptographic tools to provide a fine-grained, single-point-of-dishonest-resistant, collusion-proof and privacy-preserving solution. We also offer chaincodes, related APIs, and invoking command lines for development. Finally, we perform detailed security analysis and performance evaluation, including the consumed time of chaincode execution and the needed on-chain storage space, and we also highlight the security and performance of related post-quantum KEM algorithms on consortium blockchain.